Analysis Correlation between Learning Motivation and Learning Outcomes of Junior High School Students In Padang - Nurul Aulia Rahmi; Rahmadhani Fitri; Ganda Hijrah Selaras; Ramadhan Sumarmin (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Education is a essential requirement for life. The need for education can be felt in all aspects of human life.  Education is inseparable from the activity of learning and the activity of  teaching and educational success is inseparable from the process of  learning and teaching. The problems often encountered in the process  of learning is the low results obtained by the learning learners.  One of the factors that influence the results of the learning outcomes is  motivation. The motivation of learning is an impuls that is in someone to  be more active and diligent in learning to achieve the desired learning  outcomes. This research is descriptive research of correlation that aims  to reveal how the correlation between motivation of learning and student  learning outcomes. This research was conducted in January in grade  VII SMPN 22 Padang lessons year 2018/2019. The sample consisted  of 30 students in one class, VII 5. Sampling technique is simple random  sampling, by drawing one class which was made of a sample.  The results of the study indicate a correlation between learning motivation and  the students' cognitive science learning outcomes with a value of r = 0,53,  the coefficient of the thitumg was 3,31 greater than the ttable of 2,02,  so it can be concluded that there is a significant correlation and positive  between learning motivation and students' IPA cognitive learning outcomes  in class VII 5 of SMPN 22 Padang.